Hybrid perovskite quantum array thin film, and preparation method and use thereof

CN115768218BActive Publication Date: 2026-10-20SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211496217.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2026-10-20
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

然而,通过溶液热铸制备的膜层厚度有限,对X射线的吸收系数低,薄膜的成像效果差

Benefits of technology

[0058]本发明提供的杂化钙钛矿量子阵列薄膜,以有机羧酸和有机胺合成的氨基羧酸盐,与卤化铵盐、卤化铅和乙烯基酰胺类高分子于溶剂中反应得到前驱体溶液,其中,乙烯基酰胺类高分子和羧酸中的羰基与Pb2+八面体中心阳离子强烈的配位作用抑制了八面体的快速聚集,使[PbI6]匀速成核,同时有机羧酸的烷基链与高分子链之间的分子间作用力能够调控前驱体溶液的黏度,形成稳定的前驱体凝胶。接着将前驱体凝胶涂覆于在基底上,加热去除溶剂即可原位构筑厚度超过50μm以上单阱宽分布且垂直基底取向的薄膜,该过程中采用刮涂的方式时,二维杂化钙钛矿的八面体、层间有机阳离子通过分子间作用力自组装,垂直于基底生长,且基于羧酸与八面体中心阳离子之间的强烈的配位作用,使得热处理过程中溶剂和羧酸从体系中匀速挥发,在乙烯基酰胺类高分子添加剂的协同作用下,形成单阱宽分布的取向量子阱结构的杂化钙钛矿量子阵列薄膜,该量子阱结构有利于抑制X射线辐照下电信号的散射。在该薄膜表面制备电极层后得到的直接型X射线探测器,因量子阱的限域作用,载流子沿着量子阱均匀传输到像素基底上,有利于对待测物体的信息进行有效收集。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115768218B_ABST
    Figure CN115768218B_ABST
Patent Text Reader

Abstract

The application discloses a hybrid perovskite quantum array film and a preparation method and application thereof, and the method comprises the following steps: reacting halogenated ammonium salt, halogenated lead, amino carboxylate and a vinylamide polymer in a solvent to obtain a precursor gel; and coating the precursor gel on a substrate and removing the solvent by heating. The amino carboxylate prepared from organic carboxylic acid and organic amine cooperates with a vinylamide polymer additive to prepare the hybrid perovskite quantum array film, and the film is used as a quantum array film layer of a direct X-ray influence detector. The hybrid perovskite quantum array film provided by the application increases the film layer thickness by adjusting the components and the preparation process on the basis of maintaining the two-dimensional hybrid perovskite single-well wide distribution and the vertical substrate orientation. The direct X-ray detector prepared based on the film has a high X-ray absorption rate, and can uniformly transport the carriers in the quantum well to the pixel substrate, thereby improving the imaging effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite technology, and in particular to a hybrid perovskite quantum array thin film, its preparation method, and its applications. Background Technology

[0002] X-ray detection is widely used in medical diagnosis, industrial non-destructive testing, security monitoring, and nuclear reaction monitoring. Currently, there are two types of X-ray detectors: indirect and direct. Direct X-ray detectors consist of a semiconductor active layer and a thin-film transistor pixel array. The principle is that the semiconductor active layer directly converts the X-rays passing through the object being measured into electrical signals. Information about the object is obtained by collecting these electrical signals and then processed to form an image. Lateral charge drift and scattering can cause distortion of the collected signal, limiting its applications.

[0003] The general structural formula for two-dimensional hybrid perovskites is A'A n-1 B n X 3n+1 Or A'2A n-1 B n X 3n+1 In this structure, A' is a large organic ligand, typically an organic ammonium cation; A is a small cation such as methylamine, formamidinium, or cesium; B is a divalent metal ion; and X is a halide anion. The metal cation and halide anion coordinate to form a [BX6] octahedron. The A-site cation is distributed in the voids created by the shared vertices of the octahedrons, with a coordination number of 12. A' bonds to the anions at the edges of the octahedrons through electrostatic attraction, forming an organic spacer layer. The dielectric constant of the spacer layer is mismatched with the octahedral sheets, causing the [BX6] octahedral layer to form a natural quantum well. n represents the well width of the quantum well, i.e., the number of octahedral layers. Carrier transport in the quantum well structure exhibits anisotropy. By controlling the reaction components and the preparation process, the vertical growth of the two-dimensional hybrid perovskite quantum well can be controlled. In the prepared film, carriers migrate directionally along the growth direction of the quantum well, while lateral drift and scattering of carriers can be suppressed. These unique properties make two-dimensional hybrid perovskites extremely valuable for high-definition imaging in the field of direct X-ray detection.

[0004] Furthermore, the exciton binding energy varies in quantum wells with different well widths, which affects the charge collection efficiency. Therefore, in addition to maintaining the vertical orientation, obtaining a quantum well with a uniform well width is the key to achieving high-definition imaging with X-ray detectors.

[0005] However, current research on the vertical substrate orientation control of two-dimensional hybrid perovskites is mostly focused on solar cells. The thickness of the hybrid perovskite film is about 0.5 μm. Films of this thickness have low absorption rates for high-energy X-rays, generate fewer charge carriers, and have weak electrical signals, affecting the final imaging clarity. In existing technologies, the aggregation rate of octahedra during the nucleation process of two-dimensional hybrid perovskites can be controlled by regulating organic ligands, solvents, and additives. At the same time, the evaporation rate of solvents and additives during film growth can be controlled to construct quantum well arrays perpendicular to the substrate orientation. However, this conventional method is prone to synthesizing multi-n quantum well films, which is not conducive to the uniform transport of charge carriers to the array substrate. In Non-Patent Literature 1, acetic acid and organic ligands are synthesized into aminocarboxylate through vacuum rotary evaporation. Then, the aminocarboxylate is combined with an organic ammonium cation at the A site and a halide at the B site to prepare a precursor of two-dimensional hybrid perovskites. The precursor solution is then spin-coated onto a hot substrate using a casting method to prepare quantum wells perpendicular to the substrate orientation. In this method, acetic acid can form a strong coordination interaction with the B-site cation, inhibiting the rapid aggregation of [BX6] octahedra. During casting, acetate ions react with excess A-site organic ammonium cations to generate a low-vapor-pressure gas. As the solvent evaporates at a uniform rate, the [BX6] octahedra slowly and uniformly aggregate, forming a thin film with a single-well width distribution and perpendicular orientation to the substrate. This method holds promise for overcoming the barrier to high-definition imaging in direct-type X-ray detectors. However, the film thickness prepared by solution thermal casting is limited, resulting in a low X-ray absorption coefficient and poor imaging performance. Increasing the film thickness to 50 μm using a blade coating technique with the aforementioned precursor solution resulted in a significant decrease in film quality after annealing, exhibiting low-well-width and randomly distributed quantum wells, thereby reducing X-ray detection efficiency.

[0006] Non-patent literature 1: Liang C, Gu H, Xia Y, et al. Two-dimensional Ruddlesden-Popper layered perovskite solar cells based on phase-pure thin films [J]. Nature Energy, 2021, 6(1): 38-45. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides a hybrid perovskite quantum array thin film for use in direct X-ray detectors and its preparation method. This invention prepares a hybrid perovskite quantum array thin film using an aminocarboxylate prepared from organic carboxylic acids and organic amines, in conjunction with vinyl amide polymer additives, and uses it as the quantum array film layer in a direct X-ray detector. The hybrid perovskite quantum array thin film provided by this invention increases the film thickness by controlling the composition and preparation process while maintaining the wide distribution of the two-dimensional hybrid perovskite single wells and its perpendicular orientation to the substrate. The direct X-ray detector prepared based on this film exhibits high X-ray absorption and can uniformly transport charge carriers from the quantum wells to the substrate, thereby effectively collecting the signal from the measured object.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] On one hand, the present invention provides a method for preparing a hybrid perovskite quantum array thin film, comprising the following steps:

[0010] (1) Ammonium halide (AX), lead halide (PbX2), aminocarboxylate and vinyl amide polymers are reacted in a solvent to obtain a precursor gel;

[0011] (2) The precursor gel obtained in step (1) is coated on the substrate, and the solvent is removed by heating to obtain the hybrid perovskite quantum array film.

[0012] In a preferred embodiment, the ammonium halide (AX') is selected from any one or more of methylaminohydroiodic acid, formamidinic hydroiodic acid, methylaminohydrobromic acid, formamidinic hydrobromic acid, methylaminohydrochloride and formamidinic hydrochloride, preferably methylaminohydroiodic acid;

[0013] Preferably, the lead halide (PbX2) is selected from any one or more of lead iodide, lead bromide and lead chloride, and is preferably lead iodide;

[0014] Preferably, the vinylamide polymer is selected from any one or more of polyvinylpyrrolidone, polyvinylformamide, polyvinylcaprolactam, and polyvinylacrylamide, and is preferably polyvinylpyrrolidone.

[0015] Preferably, the solvent is a mixture of dimethyl sulfoxide and N,N-dimethylformamide;

[0016] Preferably, the solvent is a mixed solvent of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 1:4 to 4:1, and more preferably a mixed solvent of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 2:3 or 1:4.

[0017] In a preferred embodiment, the method for preparing the aminocarboxylate salt includes the steps of reacting an organic carboxylic acid and an organic amine in an ice-water bath and then rotary evaporating under reduced pressure.

[0018] Preferably, the organic carboxylic acid is selected from any one or more of acetic acid, propionic acid, n-butyric acid, isobutyric acid and n-valeric acid, and more preferably, any one or a mixture of propionic acid and n-butyric acid is used.

[0019] Preferably, the organic amine is selected from any one or more of n-butylamine, isobutylamine, α-phenylethylamine, allylamine, and 2-thioethylamine;

[0020] Preferably, the molar ratio of the organic carboxylic acid to the organic amine is 1:2 to 2:1;

[0021] Preferably, the reaction time in the ice-water bath is 1 to 4 hours;

[0022] Preferably, the temperature of the vacuum rotary evaporation is 60–100°C, more preferably 70–90°C;

[0023] Preferably, it also includes a post-processing operation of recrystallization.

[0024] In some specific embodiments, the preparation method of the aminocarboxylate involves stirring an organic carboxylic acid and an organic amine in an ice-water bath for 2 hours until they are mixed evenly. The mixture is then transferred to a rotary evaporator under reduced pressure and evaporated at 60–100°C, preferably 70–90°C, to remove the solvent. The distilled product is collected. The resulting crystalline product is washed with diethyl ether, dissolved again in ethanol, and recrystallized three times with diethyl ether. The resulting crystalline product is then dissolved in ethanol again and evaporated under reduced pressure at 60–100°C, preferably 70–90°C, to remove the solvent. The collected liquid product is the high-purity aminocarboxylate, which is then allowed to cool naturally for later use.

[0025] In a preferred embodiment, in step (1), the equation for the reaction in the solvent is shown in equation (I):

[0026] 2A'Oc+(n+1)AX'+nPbX2——→A'2X'A (n-1) Pb n X (3n+1) +2X'Oc↑(I)

[0027] In formula (I): A'Oc is an aminocarboxylate, A' is an organic ammonium ion, Oc is an organic carboxylate ion; AX' is an ammonium halide, X' is a halide ion; PbX2 is lead halide, X is a halide ion; n = 2 to 10, preferably 4 to 10;

[0028] Preferably, the ammonium halide is methylaminohydroiodic acid, and the lead halide is lead iodide. The reaction equation shown in formula (I) is shown in formula (II):

[0029] 2A'Oc+(n+1)MAI+nPbI2——→A'2MA (n-1) Pb n I (3n+1) +2MAOc↑(II)

[0030] In formula (II): A'Oc is an aminocarboxylate, A' is an organic ammonium ion, Oc is an organic carboxylate ion; MAI is methylamine hydroiodate; PbI2 is lead iodide; n = 2 to 10, preferably 4 to 10;

[0031] Preferably, the concentration of lead iodide in the reaction system is 0.5–4.5 mol / L, more preferably 2.5–4 mol / L;

[0032] In the technical solution of this invention, the vinyl amide polymer does not participate in the reaction; the carbonyl group in its molecule and the carbonyl group in Oc synergistically interact with Pb. 2+ The formation of an intermediate with significant steric hindrance inhibits the rapid aggregation of [PbI6] octahedra, reducing the growth rate and resulting in a highly crystalline and oriented thin film. Therefore, the vinyl amide polymers in this invention are additives, specifically inducing molecules for intermediate formation, and are only adsorbed in small amounts on the perovskite crystal surface; they are not considered as reactants.

[0033] Preferably, the amount of the vinylamide polymer added is A'2X'A. (n-1) Pb n X (3n+1) 1% to 5% of the total mass, for example, 1%, 2%, 3%, 4%, 5% or any value between them, preferably 1.5% to 2%;

[0034] Preferably, in step (1), the reaction in the solvent is carried out at 60-100°C with stirring for 1-4 hours; more preferably, it is carried out at 70-80°C with stirring for 1-2 hours.

[0035] In a preferred embodiment, in step (2), the coating is applied by scraping.

[0036] Preferably, the height of the scraper is 50–300 μm, and more preferably 150–200 μm.

[0037] In some specific embodiments, the substrate needs to be pretreated. The pretreatment involves ultrasonically washing with deionized water, acetone, ethanol and isopropanol in sequence, drying with nitrogen, and cleaning in an ultraviolet ozone cleaner for 0 to 20 minutes, preferably 10 to 15 minutes.

[0038] In a preferred embodiment, in step (2), the heating is a programmed temperature rise;

[0039] Preferably, the programmed temperature rise includes the following temperature rise process in sequence:

[0040] (i) Heat at 30°C for 2 to 10 hours, preferably 8 hours;

[0041] (ii) Heat at 35°C for 2–10 hours, preferably 8 hours;

[0042] (iii) Heat at 45℃ for 2 to 12 hours, preferably 10 hours;

[0043] (iii) Heat at 95℃ for 0.5 to 2 hours, preferably 1.5 hours;

[0044] (iv) Heat at 110℃ for 2 to 8 hours, preferably 6 hours.

[0045] In the technical solution of this invention, programmed temperature rise can control the evaporation rate of the solvent, which is beneficial for forming a high-quality thin film with carrier confinement of quantum array.

[0046] In another aspect, the present invention provides a hybrid perovskite quantum array thin film obtained by the above preparation method.

[0047] In another aspect, the present invention provides the use of the above-described hybrid perovskite quantum array thin film in the fabrication of a direct X-ray detector.

[0048] In another aspect, the present invention provides a direct X-ray detector, comprising a substrate, a quantum array film layer grown in situ vertically on the substrate, and an electrode layer formed on the quantum array film layer, wherein the quantum array film layer is composed of the above-mentioned hybrid perovskite quantum array thin film, and the electrode layer is formed on the surface of the quantum array film layer opposite to the substrate.

[0049] Preferably, the substrate is an indium tin oxide substrate.

[0050] Preferably, the electrode layer is selected from at least one of carbon electrodes and metal electrodes, wherein the metal is selected from at least one of gold, silver and copper.

[0051] Preferably, the method for preparing the electrode layer includes the following steps:

[0052] Carbon paste is coated onto the quantum array film and then cured.

[0053] or,

[0054] Metal is deposited on the quantum array film by thermal evaporation.

[0055] In some specific implementations, patterned electrode layers can be fabricated using a mask.

[0056] Preferably, the curing is performed at 80–120°C for 5–15 minutes, and more preferably at 90–110°C for 10–12 minutes.

[0057] The above technical solution has the following advantages or beneficial effects:

[0058] The hybrid perovskite quantum array thin film provided by this invention uses an aminocarboxylate synthesized from organic carboxylic acids and organic amines, which reacts with ammonium halide salts, lead halides, and vinyl amide polymers in a solvent to obtain a precursor solution. The carbonyl groups in the vinyl amide polymers and carboxylic acids react with Pb... 2+ The strong coordination of the octahedral central cation inhibits the rapid aggregation of octahedrons, enabling uniform nucleation of [PbI6]. Simultaneously, the intermolecular forces between the alkyl chains of the organic carboxylic acid and the polymer chains regulate the viscosity of the precursor solution, forming a stable precursor gel. The precursor gel is then coated onto a substrate, and the solvent is removed by heating, allowing for the in-situ construction of a single-well wide-distribution film with a thickness exceeding 50 μm and perpendicular orientation to the substrate. During this process, when using a blade coating method, the octahedrons of the two-dimensional hybrid perovskite and the interlayer organic cations self-assemble through intermolecular forces, growing perpendicular to the substrate. Furthermore, the strong coordination between the carboxylic acid and the octahedral central cation ensures that the solvent and carboxylic acid evaporate uniformly from the system during heat treatment. With the synergistic effect of vinylamide polymer additives, a hybrid perovskite quantum array film with a single-well wide-distribution oriented quantum well structure is formed. This quantum well structure is beneficial for suppressing the scattering of electrical signals under X-ray irradiation. The direct X-ray detector obtained after fabricating an electrode layer on the surface of the thin film has the effect of quantum well confinement, which allows charge carriers to be uniformly transported along the quantum well to the pixel substrate, thus facilitating the effective collection of information about the object under test.

[0059] Compared with the prior art, the present invention has the following advantages:

[0060] (1) Compared to existing technologies that are only suitable for films with a thickness of 500 nm, increasing the film thickness can lead to the inability to remove the liquid film solvent in a short time, resulting in a decrease in film quality. The hybrid perovskite quantum array film provided by this invention, in conjunction with aminocarboxylate and vinyl amide polymers and Pb 2+The interaction between these elements enabled the growth of quantum well films perpendicular to the substrate, with uniform and narrow well widths and thicknesses exceeding 50 μm, while significantly improving film quality. Among these, aminocarboxylate is key to ensuring the vertical orientation of the quantum well film, while the synergistic effect of the carbonyl groups in vinyl amide polymers is crucial for constructing films with uniform well widths exceeding 50 μm. The resulting direct-type X-ray detector exhibits strong X-ray absorption, reduces lateral scattering of charge carriers during X-ray imaging, achieves directional transmission, and efficiently collects electrical signals.

[0061] (2) In the prior art, the high-temperature annealing used in conventional hot casting methods causes the solvent on the surface of the liquid film to evaporate rapidly. The perovskite quantum wells preferentially crystallize on the surface, forming a dense solid film, which closes the solvent evaporation channels and prevents the solvent in the bottom layer from evaporating, resulting in a sharp decline in film quality. However, the programmed temperature rise used in this invention utilizes long-term low-temperature drying and subsequent high-temperature annealing to control the evaporation of solvent in the micron-sized liquid film. This can ensure the solvent evaporation channels for a longer period of time. Furthermore, due to the inhibitory crystallization effect of aminocarboxylate and vinylamide polymers, the solvent evaporates uniformly, ultimately constructing a high-quality micron-sized film with vertical and uniform well width. Attached Figure Description

[0062] Figure 1 These are fluorescence spectra of the hybrid perovskite quantum array thin films prepared in the examples and comparative examples.

[0063] Figure 2 These are X-ray diffraction patterns of the hybrid perovskite quantum array thin films prepared in the examples and comparative examples.

[0064] Figure 3 The image shows the It response curves of the direct-type X-ray detectors prepared in the examples and comparative examples under a 50kVp X-ray switch. Detailed Implementation

[0065] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0066] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.

[0067] Example 1

[0068] This embodiment provides a direct X-ray detector, the fabrication process of which includes the following steps:

[0069] ① Acetic acid and phenylethylamine organic ligand (A') in a molar ratio of 1:1 were stirred in an ice-water bath at 0℃ for 2 hours to mix evenly; then the crude product was transferred to a rotary evaporator under reduced pressure and evaporated at 60℃ for 1 hour to remove the solvent, and the distilled product was collected; the crystalline product was then washed three times with diethyl ether, dissolved again with ethanol, and recrystallized three times with diethyl ether; the crystalline product was dissolved again in ethanol and evaporated under reduced pressure at 60℃ for 1 hour, and the collected liquid product was high-purity phenylethylamine carboxylate, which was cooled to room temperature for later use;

[0070] ② Phenethylamine carboxylate (PEAAc), methylamine hydroiodide (MAI), lead iodide (PbI2), and polyvinylpyrrolidone were dissolved in a mixed solvent of dimethyl sulfoxide and N,N-dimethylformamide (the volume ratio of dimethyl sulfoxide to N,N-dimethylformamide was 1:4). The mixture was heated and stirred at 70°C for 2 hours, and then cooled to obtain a precursor gel. The molar ratio of phenylethylamine carboxylate, methylamine hydroiodide (MAI), and lead iodide (PbI2) was 2:6:5, the amount of polyvinylpyrrolidone added was 9.6 mg, the concentration of lead iodide in the solvent was 3.5 mol / L, and the total volume of the reaction system was 0.2 mL.

[0071] ③ The indium tin oxide substrate was washed successively with deionized water, acetone, ethanol and isopropanol in an ultrasonic cleaner, dried with nitrogen gas, and then cleaned in a UV ozone cleaner for 15 min. Then, the precursor gel was dropped onto the indium tin oxide substrate, and the doctor blade was moved to a height of 200 μm to form a uniform film layer on the substrate. The coating machine was programmed to heat at 30℃ for 8 h, 35℃ for 8 h, 45℃ for 11 h, 95℃ for 1.5 h, and 110℃ for 2 h to finally obtain a hybrid perovskite quantum array thin film with a thickness of 60 μm.

[0072] ④ A direct X-ray detector was prepared by using a hybrid perovskite quantum array thin film as the quantum array thin film and depositing copper electrodes on its surface by thermal evaporation.

[0073] The hybrid perovskite quantum array thin film prepared in this embodiment exhibits a single well width distribution. Figure 1 ), high crystallinity and vertical orientation ( Figure 2 The resulting X-ray detector has the highest X-ray photocurrent. Figure 3 ).

[0074] Comparative Example 1

[0075] The direct X-ray detector provided in this comparative example is prepared in the same way as in Example 1, except that step ① is omitted and phenylethylamine carboxylate (PEAAc) in step ② is replaced with the same amount of phenylethylamine hydroiodide.

[0076] The thickness of the hybrid perovskite quantum array film in this comparative example is 60 μm. The hybrid perovskite PL prepared in this example has a lower strength than that in the previous example, and exhibits two well widths with n=4 and 5. Figure 1 The crystallinity decreased significantly, and diffraction peaks of randomly oriented perovskite were present. Figure 2 As an X-ray detector, it has a lower X-ray photocurrent, approximately half that of Example 1. Figure 3 ).

[0077] Comparative Example 2

[0078] The direct X-ray detector provided in this comparative example is prepared in the same way as in Example 1, except that polyvinylpyrrolidone is not added in step ②.

[0079] The thickness of the hybrid perovskite quantum array film in this comparative example is 60 μm. Compared with Example 1, this comparative example lacks polyvinylpyrrolidone, resulting in a film with a well width mainly of n=1, while also exhibiting weak PL peaks at n=2, 3, 4, and 5. The crystallinity is poor, and due to the presence of the low-well-width phase, its X-ray diffraction pattern shows obvious randomly oriented two-dimensional hybrid perovskite impurities. The obtained X-ray detector has significant baseline drift, which is not conducive to efficient collection of photogenerated signals.

[0080] Effect verification

[0081] To verify the effectiveness of the present invention, the hybrid perovskite quantum array thin films prepared in the examples and comparative examples were characterized by fluorescence spectroscopy with an excitation wavelength of 365 nm. The results are as follows: Figure 1 As shown: In Example 1, the quantum well width is concentrated at n=5, which conforms to the stoichiometry of the raw materials. In Comparative Example 1, the peak at n=5 is broad and has low intensity, while the well width is clearly distributed at n=4. In Comparative Example 2, the quantum well width is mainly distributed at n=1, with quantum wells also present at n=2, 3, 4, and 5. This indicates that only with the synergistic effect of PEAAc and polyvinylpyrrolidone can a quantum well film with a uniform well width distribution be prepared.

[0082] To verify the effectiveness of the present invention, X-ray diffraction patterns were used to characterize the hybrid perovskite quantum array films prepared in the examples and comparative examples. The results are as follows: Figure 2As shown: In Example 1, there are three distinct characteristic peaks of the vertically oriented two-dimensional hybrid perovskite quantum well, representing crystal planes (111), (202), and (313), respectively. In Comparative Example 1, the peak intensities of these three characteristic peaks are significantly reduced, and randomly oriented perovskite characteristic peaks are present, marked with "*" in the figure. The peak intensity in Comparative Example 2 is slightly lower than that in Example 1, but significantly stronger than that in Comparative Example 1, and also contains randomly oriented perovskite impurities. This indicates that PEAAc is key to constructing vertically oriented perovskite quantum wells; it can synergistically interact with polyvinylpyrrolidone to eliminate low-well-width quantum wells, thereby obtaining highly crystalline and vertically oriented quantum well films.

[0083] To verify the synergistic effect of PEAAc and polyvinylpyrrolidone, the X-ray detectors prepared in the examples and comparative examples were directly placed under a 50 kVp X-ray switch and a 30 V bias voltage, and the It curves were measured. The X-ray response of films with different well width distributions was compared, and the results are as follows: Figure 3 As shown: In Example 1, the detector prepared by the synergistic use of PEAAc and polyvinylpyrrolidone exhibits the strongest X-ray response, lower dark current, and a stable baseline, indicating that the synergistic effect of PEAAc and polyvinylpyrrolidone can improve the film quality, thereby enhancing the X-ray detection performance.

[0084] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a hybrid perovskite quantum array thin film, characterized in that, Includes the following steps: (1) The ammonium halide (AX'), lead halide (PbX2), aminocarboxylate and vinyl amide polymers are reacted in a solvent to obtain a precursor gel; (2) The precursor gel obtained in step (1) is coated on the substrate, and the solvent is removed by heating to obtain the hybrid perovskite quantum array film. In step (2), the heating is a programmed temperature rise; the programmed temperature rise includes the following heating processes in sequence: (i) Heat at 30℃ for 2~10 h; (ii) Heat at 35℃ for 2~10 h; (iii) Heat at 45℃ for 2~12 h; (iii) Heat at 95℃ for 0.5~2 h; (iv) Heat at 110℃ for 2~8 h; The ammonium halide salt (AX') is selected from any one or more of methylaminohydroiodic acid, formamidin hydroiodic acid, methylaminohydrobromic acid, formamidin hydrobromic acid, methylamino hydrochloride, and formamidin hydrochloride; The vinylamide polymers are selected from any one or more of polyvinylpyrrolidone, polyvinylformamide, polyvinylcaprolactam, and polyvinylacrylamide; The method for preparing the aminocarboxylate includes the steps of reacting an organic carboxylic acid and an organic amine in an ice-water bath and rotary evaporating under reduced pressure; the organic carboxylic acid is selected from any one or more of acetic acid, propionic acid, n-butyric acid, isobutyric acid and n-valeric acid; the organic amine is selected from any one or more of n-butylamine, isobutylamine, α-phenylethylamine, allylamine and 2-thio-ethylamine.

2. The preparation method according to claim 1, characterized in that, The ammonium halide (AX') is methylaminohydroiodic acid.

3. The preparation method according to claim 1, characterized in that, The lead halide (PbX2) is selected from any one or more of lead iodide, lead bromide and lead chloride.

4. The preparation method according to claim 3, characterized in that, The lead halide (PbX2) is lead iodide.

5. The preparation method according to claim 1, characterized in that, The vinylamide polymer is polyvinylpyrrolidone.

6. The preparation method according to claim 1, characterized in that, The solvent is a mixture of dimethyl sulfoxide and N,N-dimethylformamide.

7. The preparation method according to claim 6, characterized in that, The solvent is a mixture of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 1:4 to 4:

1.

8. The preparation method according to claim 7, characterized in that, The solvent is a mixture of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 2:3 or 1:

4.

9. The preparation method according to claim 1, characterized in that, The organic carboxylic acid is any one or a mixture of propionic acid and butyric acid.

10. The preparation method according to claim 1, characterized in that, The molar ratio of the organic carboxylic acid and the organic amine is 1:2 to 2:

1.

11. The preparation method according to claim 1, characterized in that, The reaction time in the ice-water bath is 1-4 hours.

12. The preparation method according to claim 1, characterized in that, The temperature for the vacuum rotary evaporation is 60~100℃.

13. The preparation method according to claim 12, characterized in that, The temperature for the vacuum rotary evaporation is 70~90℃.

14. The preparation method according to claim 1, characterized in that, The preparation method of the aminocarboxylate also includes a recrystallization post-processing step.

15. The preparation method according to claim 1, characterized in that, In step (1), the equation for the reaction in the solvent is shown in equation (I): (I) In formula (I): A'Oc is an aminocarboxylate, A' is an organic ammonium ion, Oc is an organic carboxylate ion; AX' is an ammonium halide, X' is a halide ion; PbX2 is lead halide, X is a halide ion; n=2~10.

16. The preparation method according to claim 15, characterized in that, n is 4 to 10.

17. The preparation method according to claim 15, characterized in that, The ammonium halide salt is methylaminohydroiodic acid, and the lead halide is lead iodide. The reaction equation shown in formula (I) is shown in formula (II): (II) In formula (II): A'Oc is aminocarboxylate, A' is organic ammonium ion, Oc is organic carboxylate ion; MAI is methylamine hydroiodate; PbI2 is lead iodide; n=2~10.

18. The preparation method according to claim 17, characterized in that, n is 4 to 10.

19. The preparation method according to claim 17, characterized in that, The concentration of lead iodide in the reaction system is 0.5~4.5 mol / L.

20. The preparation method according to claim 19, characterized in that, The concentration of lead iodide in the reaction system is 2.5~4 mol / L.

21. The preparation method according to claim 15, characterized in that, The amount of vinylamide polymer added is 1% to 5% of the total mass.

22. The preparation method according to claim 21, characterized in that, The amount of vinylamide polymer added is 1.5% to 2% of the total mass.

23. The preparation method according to claim 1, characterized in that, In step (1), the reaction in the solvent is carried out at 60~100℃ with stirring for 1~4 h.

24. The preparation method according to claim 23, characterized in that, In step (1), the reaction in the solvent is carried out at 70~80℃ with stirring for 1~2 h.

25. The preparation method according to claim 1, characterized in that, In step (2), the coating is applied by scraping.

26. The preparation method according to claim 25, characterized in that, The height of the scraper used for coating is 50~300 μm.

27. The preparation method according to claim 26, characterized in that, The height of the scraper used for coating is 150~200 μm.

28. The preparation method according to claim 1, characterized in that, In step (2), the programmed temperature rise includes the following temperature rise process in sequence: (i) Heat at 30°C for 8 hours; (ii) Heat at 35℃ for 8 hours; (iii) Heat at 45℃ for 10 h; (iii) Heat at 95℃ for 1.5 h; (iv) Heat at 110℃ for 6 h.

29. The hybrid perovskite quantum array thin film obtained by any of the preparation methods according to claims 1-28.

30. Use of the hybrid perovskite quantum array thin film of claim 29 in the fabrication of a direct-type X-ray detector.

31. A direct-type X-ray detector, characterized in that, The invention includes a substrate, a quantum array film grown in situ vertically on the substrate, and an electrode layer formed on the quantum array film, wherein the quantum array film is composed of the hybrid perovskite quantum array thin film of claim 29, and the electrode layer is formed on the surface of the quantum array film opposite to the substrate.

32. The direct-type X-ray detector according to claim 31, characterized in that, The substrate is an indium tin oxide substrate.

33. The direct-type X-ray detector according to claim 31, characterized in that, The electrode layer is selected from at least one of carbon electrodes and metal electrodes, and the metal is selected from at least one of gold, silver and copper.

34. The direct-type X-ray detector according to claim 33, characterized in that, The method for preparing the electrode layer includes the following steps: Carbon paste is coated onto the quantum array film and then cured. or, Metal is deposited on the quantum array film by thermal evaporation.

35. The direct-type X-ray detector according to claim 34, characterized in that, Patterned electrode layers are fabricated using a photomask during electrode layer fabrication.

36. The direct-type X-ray detector according to claim 34, characterized in that, The curing process involves curing at 80-120℃ for 5-15 minutes.

37. The direct-type X-ray detector according to claim 36, characterized in that, The curing process involves curing at 90~110℃ for 10~12 minutes.

Citation Information

Patent Citations

  • Direct X-ray image detector and preparation method thereof

    CN114252031A

  • Perovskite solid-phase precursor and preparation method thereof, and preparation and application of perovskite material

    CN115073297A